Clinical and Biochemical Outcomes of Patients with Alcohol Dependence Syndrome during Inpatient Management: A Prospective Observational Study (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Alcohol Dependence Syndrome (ADS) is a chronic relapsing disorder associated with significant physical, psychological, and socioeconomic burden. Prospective evidence on short-term clinical and biochemical outcomes during inpatient management in South Indian tertiary care settings is limited. Objective: To evaluate changes in alcohol withdrawal severity and assess clinical and biochemical outcomes among hospitalized patients with ADS. Methods: A prospective observational study will be conducted over six months in the Departments of Psychiatry and General Medicine of a tertiary care teaching hospital. Approximately 100 adult patients diagnosed with ADS will be enrolled after obtaining informed consent and Institutional Ethics Committee approval. Withdrawal severity will be assessed using the Clinical Institute Withdrawal Assessment for Alcohol-Revised (CIWA-Ar), dependence severity using the Severity of Alcohol Dependence Questionnaire (SADQ), and alcohol use using the Alcohol Use Disorders Identification Test (AUDIT). The primary outcome is change in CIWA-Ar score from admission to discharge. Secondary outcomes include duration of hospital stay, withdrawal-related complications, adverse drug reactions, discharge status, and changes in liver function, renal function, hematological, electrolyte, and glucose parameters. Data will be analyzed using descriptive and inferential statistics with 95% confidence intervals and p
Keywords: Alcohol Dependence Syndrome (ADS); CIWA-Ar score; Alcohol Dependence Questionnaire (SADQ)